CAMP signalling of Bordetella adenylate cyclase toxin through the SHP‐1 phosphatase activates the BimEL‐Bax pro‐apoptotic cascade in phagocytes. (7th October 2015) - Ahmad, Jawid Nazir; Cerny, Ondrej; Linhartova, Irena; Masin, Jiri; Osicka, Radim; Sebo, Peter
Summary: The adenylate cyclase toxin‐hemolysin (CyaA, ACT or AC‐Hly) plays a key role in virulence of Bordetella pertussis . CyaA penetrates myeloid cells expressing the complement receptor 3 (αM β2 integrin CD11b/CD18) and subverts bactericidal capacities of neutrophils and macrophages by catalysing unregulated conversion of cytosolic ATP to the key signalling molecule adenosine 3', 5'‐cyclic monophosphate (cAMP). We show that the signalling of CyaA‐produced cAMP hijacks, by an as yet unknown mechanism, the activity of the tyrosine phosphatase SHP‐1 and activates the pro‐apoptotic BimEL‐Bax cascade. Mitochondrial hyperpolarization occurred in human THP‐1 macrophages within 10 min of exposure to low CyaA concentrations (e.g. 20 ng ml −1 ) and was accompanied by accumulation of BimEL and association of the pro‐apoptotic factor Bax with mitochondria. BimEL accumulation required cAMP/protein kinase A signalling, depended on SHP‐1 activity and was selectively inhibited upon small interfering RNA knockdown of SHP‐1 but not of the SHP‐2 phosphatase. Moreover, signalling of CyaA‐produced cAMP inhibited the AKT/protein kinase B pro‐survival cascade, enhancing activity of the FoxO3a transcription factor and inducing Bim transcription. Synergy of FoxO3a activation with SHP‐1 hijacking thus enables the toxin to rapidly trigger a persistent accumulation of BimEL, thereby activating the pro‐apoptotic programme of macrophages and subverting the innate immunity of the host.